Spatial Distribution and Evolution of pH as a Function of Cation Exchange Capacity, Sum of Exchangeable Bases, and Organic Matter and Aluminum in the Soils of Foumban - Vivien Piercy Lotse Tedontsah; Michel Bertrand Mbog; Lionelle Bitom-Mamdem; Gilbert François Ngon Ngon; Robert Christel Edzoa; Bernard Tassongwa; Dieudonné Bitom; Jacques Etame (Applied and Environmental Soil Science)
Foumban, located in the Noun valley in western Cameroon, is a prime location for food production. However, this locality is experiencing a significant decline in productivity due to the acidity of its soil. This acidity is linked to the behaviour of certain soil properties essential for plant growth. The present work aims to study the behaviour of pH as a function of certain chemical parameters such as CEC, organic matter, exchangeable bases, and exchangeable aluminum and to map the spatial structure of the pH parameter by kriging. To achieve this objective, ninety soil samples were taken in the locality of Foumban and sent to the soil laboratory where physicochemical analyses were carried out. The results obtained were processed by statistical and geostatistical software. This made it possible to establish relationships between pH and other soil properties. The obtained R2 results show that pH-exchangeable aluminum and pH sum of bases are strongly correlated while pH-CEC and pH-organic matter are weakly correlated. For the spatial distribution of pH, the Gaussian model was applied to fit the experimental semivariogram. The low values of the semivariogram of the pH-water contents obtained overall reflect a strong correlation of the values. The spatial structure obtained after kriging defines two groups of soils in the study area according to their acidity: acidic soils which cover about 82.4% of the study area and moderately acidic soils which occupy about 17.6% of the study area. Finally, it appears that acidity remains a real problem for the soils of Foumban. The risks of aluminum toxicity should not be overlooked. The rate of use of ammonia fertiliser in the study area should be reduced, especially in soils with a pH below 5.4. The use of strong base inputs such as calcium carbonate (CaCO3) or calcium hydroxide (Ca (OH)2) at normal doses is strongly recommended in acid soils.